Exploring factors that mitigate the continued influence of misinformation - Irene P. Kan (SpringerOpen, 2021)
Abstract Background The term “continued influence effect” (CIE) refers to the phenomenon that discredited and obsolete information continues to affect behavior and beliefs. The practical relevance of this work is particularly apparent as we confront fake news everyday. Thus, an important question becomes, how can we mitigate the continued influence of misinformation? Decades of research have identified several factors that contribute to the CIE reduction, but few have reported successful elimination. Across three studies, we evaluated the relative contribution of three factors (i.e., targeting the misinformation, providing an alternative explanation, and relative importance of the misinformation content) to the reduction of the CIE. Results Across three studies and two different CIE measures, we found that alternative provision consistently resulted in CIE reduction. Furthermore, under certain conditions, the combination of alternative inclusion and direct targeting of misinformation in the correction statement resulted in successful elimination of the CIE, such that individuals who encountered that type of correction behaved similarly to baseline participants who never encountered the (mis)information. In contrast, under one CIE measure, participants who received correction statements that failed to include those elements referenced the (mis)information as frequently as baseline participants who never encountered a correction. Finally, we delineated several component processes involved in misinformation outdating and found that the extent of outdating success varied as a function of the causality of misinformation. Conclusions The damaging effects of fake news are undeniable, and the negative consequences are exacerbated in the digital age. Our results contribute to our understanding of how fake news persists and how we may begin to mitigate their effects.